Evaluating functional recovery following proximal femoral nail fixation in proximal femoral fractures: a study from a developing nation - Kumar, Raj; Sindhu, Gur-Aziz S.; Singh, Manavdeep; Pattnaik, Saphalya (International Journal of Research in Orthopaedics, 2025)
Background: Intramedullary fixation systems have become increasingly favoured over conventional dynamic hip screws in the treatment of proximal femoral fractures. This shift is attributed to several key benefits, including reduced soft tissue trauma, shorter operative times, and enhanced biomechanical properties. Methods: A prospective randomised study was carried out at Dayanand Medical College and Hospital Ludhiana, India between January 2016 and January 2017, with proximal femoral fractures. Exclusion criteria included paediatric cases, pathological or neglected fractures, periprosthetic fractures, and femoral neck fractures. The primary aim was to evaluate fracture union and functional recovery, while secondary outcomes focused on identifying any postoperative complications. Results: Among the 35 participants (19 males and 16 females), the average age was 59.8 years. Subtrochanteric fractures were more prevalent in older individuals, with a higher incidence on the left side. Domestic falls accounted for 52% of the injuries, while 48% resulted from road traffic accidents. The surgical procedure involved an average blood loss of 197 ml and lasted approximately 142 minutes. Fracture union was achieved in 95.23% of the cases, while implant failure was observed in 9.52%. Functional assessments showed that 68% of patients had excellent to good recovery outcomes, with minimal complications reported postoperatively. Conclusions: Proximal femoral nail (PFN) provides secure fixation with high union rate and positive functional outcomes reinforcing its preference over traditional extramedullary fixation methods. Further comparative analyses are required with larger sample sizes to refine the choice of fixation for different fracture types.